Fatigue Evaluation of Steel Bridge Details Integrating Multi-Scale Dynamic Analysis of Coupled Train-Track-Bridge System and Fracture Mechanics - Huile Li; Gang Wu (Applied Sciences, 2020)
Increased running speed and axle weight in the transportation network lead to significant dynamic interactions between the vehicles and bridges. It is essential to capture these interactions in fatigue analysis of steel bridges. This paper presents a framework for fatigue evaluation of critical steel bridge details through multi-scale dynamic analysis of the train-track-bridge system and linear elastic fracture mechanics. The multi-scale coupled dynamic analysis allows accurate and efficient computation of fatigue stresses produced by the moving trains in structural details based on a vehicle-bridge analysis model composed of a 3D vehicle model, multi-scale bridge finite element model including the track system, and a wheel–rail interaction model. Field data from an existing steel-truss railway bridge are used to validate the multi-scale analysis method. Enhanced fatigue evaluation of the bridge detail is performed using the computed fatigue load effects and linear elastic fracture mechanics. The effects of the track irregularity and operating train speed on fatigue crack propagation life are investigated. The presented framework is general and can be applied to other types of steel bridges such as the steel-box girder bridge with orthotropic decks.